The Influence of Competence, Religiosity, and Work Motivation on the Performance of Fishermen Through Work Ethic as an Intervening Variable - Yusnar, Muhammad; Sugianto, Sugianto; Ridwan, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Performance is the work accomplished by an individual in doing the work commanded based on abilities and experience. Islam teaches that work must be done not only to fulfill the needs of the world but also as a means of worshiping Allah SWT. This research aims to analyze the effect of competence, religiosity, and work motivation on the performance of fishermen in Sei Apung Jaya village with work ethic as an intervening variable. The study is quantitive with a survey approach of 97 respondents. The data analysis method used is path analysis with the SPSS version 20 program. The results of the study found that competence and work motivation had a significant effect on work ethic. Religiosity has no effect on work ethic. Competence, work motivation, and work ethic have a significant effect on performance. Religiosity has no effect on performance. Competence, religiosity, and work motivation have no effect on performance through work ethic as an intervening variable.